Effect of Aggressive Experience in Female Syrian Hamsters on Glutamate Receptor Expression in the Nucleus Accumbens - Borland, Johnathan M.; Kim, Ellen; Swanson, Samuel P.; Rothwell, Patrick E.; Mermelstein, Paul G.; Meisel, Robert L. (Frontiers in Behavioral Neuroscience, 2020)
Our social relationships determine our health and well-being. In rodent models, there is now strong support for the rewarding properties of aggressive or assertive behaviors to be critical for the expression and development of adaptive social relationships, buffering from stress and protecting from the development of psychiatric disorders such as depression. However, due to the false belief that aggression is not a part of the normal repertoire of social behaviors displayed by females, almost nothing is known about the neural mechanisms mediating the rewarding properties of aggression in half the population. In the following study, using Syrian hamsters as a well-validated and translational model of female aggression, we investigated the effects of aggressive experience on the expression of markers of postsynaptic structure (PSD-95, Caskin I) and excitatory synaptic transmission (GluA1, GluA2, GluA4, NR2A, NR2B, mGluR1a and mGluR5) in the nucleus accumbens, caudate putamen and prefrontal cortex. Aggressive experience resulted in an increase in PSD-95, GluA1 and the dimer form of mGluR5 specifically in the nucleus accumbens 24 hours following aggressive experience. There was also an increase in the dimer form of mGluR1a 1 week following aggressive experience. Aggressive experience also resulted in an increase in the strength of the association between these postsynaptic proteins and glutamate receptors, supporting a common mechanism of action. In addition, one week following aggressive experience there was a positive correlation between the monomer of mGluR5 and multiple AMPAR and NMDAR subunits. In conclusion, we provide evidence that aggressive experience in females results in an increase in the expression of postsynaptic density, AMPARs and group I metabotropic glutamate receptors, and an increase in the strength of the association between postsynaptic proteins and glutamate receptors. This suggests that aggressive experience may result in an increase in excitatory synaptic transmission in the nucleus accumbens, potentially encoding the rewarding and behavioral effects of aggressive interactions.